The Analysis of Interpersonal Function in BTS’ Speech at UNGA 2020 - Khairunnisa Wintara; Nurlela Nurlela; Ely Hayati Nasution (Talenta Publisher, 2022)
This article investigates the Interpersonal function in the speech by BTS at the 75th UN General Assembly. The objective is to find out the Mood types and to describe the Interpersonal function realized in BTS’ speech. Qualitative method is used in this study. The data were collected from the clauses in BTS’ speech at UNGA. Through this study, it is found that the Mood types in BTS’ speech at UNGA are Declarative mood (92,30%), Imperative mood (6,59%), and Interrogative mood (1,09%). The findings also revealed the dominant Mood types is Declarative which is used to share or to give information to the audience. For the Interpersonal function, it is realized through Mood structures which contains the Mood and Residue elements. Through Mood elements, it is found that there are Subject, Finite, and Mood Adjunct. While in Residue elements, there are Predicator, Complement, and Circumstantial Adjunct.